Left main coronary artery compression in pulmonary hypertension. Issue 7 (25th November 2020) - Labin, Jonathan E.; Saggar, Rajan; Yang, Eric H.; Lluri, Gentian; Sayah, David; Channick, Richard; Ardehali, Abbas; Aksoy, Olcay; Parikh, Rushi V.
Abstract: Extrinsic compression of the left main coronary artery (LMCA) by a dilated pulmonary artery (PA) in the setting of pulmonary arterial hypertension (PAH) is an increasingly recognized disease entity. LMCA compression has been associated with angina, arrhythmia, heart failure, and sudden cardiac death in patients with PAH. Recent studies suggest that at least 6% of patients with PAH have significant LMCA compression. Screening for LMCA compression can be achieved with computed coronary tomography angiography, with a particular emphasis on assessment of PA size and any associated downward displacement and reduced takeoff angle of the LMCA. Indeed, evidence of a dilated PA (>40 mm), a reduced LMCA takeoff angle (<60°), and/or LMCA stenosis on CCTA imaging should prompt further diagnostic evaluation. Coronary angiography in conjunction with intravascular imaging has proven effective in diagnosing LMCA compression and guiding subsequent treatment. While optimal medical therapy and surgical correction remain in the clinician's arsenal, percutaneous coronary intervention has emerged as an effective treatment for LMCA compression. Given the prevalence of LMCA compression, its associated morbidity, and mortality, and the wide array of successful treatment strategies, maintaining a high degree of suspicion for this condition, and understanding the potential treatment strategies is critical.